Startup Entrepreneurial Creativity and Impact in Armenia: Case Study (2015–2018). Issue 1 (June 2020) - Keshishyan, Elizabeth; Boghosian, Mary-Hrachoohi
The entrepreneurial creativity (EC) is an important factor for measuring the health and the well-being of the entrepreneurial ecosystem in any country. The purpose of our study was to examine the status of the Armenia's entrepreneurial ecosystem through entrepreneurial creativity (EC) framework. The 'Entrepreneurial Creativity and Growth' (EC&G) model developed by Petrakis and Kafka (2016) was adopted. This model puts forward seven factors affecting the entrepreneurial creativity (EC), therefore, no other factor outside this framework was considered. Partial least square (PLS) methodology was applied to construct a predictive model of the seven factors dependencies on the (EC) and on each other. To increase granularity of the model, two to four sub-factors were constructed for each factor sufficient to affect the main dependent variable, the EC. Only two of the factors 'Culture and Personal Characteristics of the entrepreneurs' ( p = 0.001) and the 'Availability of Relevant Institutions' ( p = 0.007) were shown to have significant effect on the EC. The 'Culture and Personality' of entrepreneurs was significantly and positively correlated to the EC ( b = 0.444), which indicated that flexibility and risk-taking is the highest characteristics of Armenia's entrepreneurs; thus, more creative. This article reports these findings and more of a study aimed at analysing the EC among the Armenian startup founders who established businesses within the years 2015–2018.